The Guns of Bull Run: A Story of the Civil War's Eve - Altsheler, Joseph A. (Joseph Alexander), 1862-1919 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Guns of Bull Run: A Story of the Civil War's Eve" by Joseph A. Altsheler is a historical novel written during the late 19th century. This book explores the tumultuous period leading up to the American Civil War, focusing on the perspectives and experiences of young characters, particularly Harry Kenton and his cousin Dick Mason. The narrative delves into their lives in a divided Kentucky, reflecting the broader societal conflict instigated by South Carolina's secession and the impending war. At the start of the story, readers are introduced to Harry Kenton and Dick Mason, who are students at Pendleton Academy. As they ponder the upcoming Christmas holiday, they are suddenly confronted with news of South Carolina's secession, which reverberates through their school and the town. The school principal, Dr. Russell, delivers the shocking letter, igniting discussions among the students about loyalty and the possibility of two divided republics. As Harry navigates his relationships, particularly with Dick, he begins to feel the weight of impending conflict and responsibility. When Harry's father, Colonel Kenton, entrusts him with a significant mission to deliver a message to South Carolina, it marks the transition from the innocence of youth to the reality of war, setting the stage for the challenges they will face ahead. (This is an automatically generated summary.)
The Civil War Series, Volume 1
Release date is 2003-01-01
Produced by Ken Reeder. HTML version by Al Haines.
Keywords: Bull Run, 1st Battle of, Va., 1861 -- Juvenile fiction